(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The goal of this article is to critically analyze the findings of the first, recently published, studies about Corporate Social Responsibility (CSR) impacts on Sustainable Human Development (SHD). We aim at deriving conclusions for effective CSR strategies and at identifying consequences for management and research. As CSR claims to create value for corporations and for society, we argue that the people-centered Capability Approach (CA) is promising to provide neglected and much needed insights how corporate activities affect individuals and communities. Based on a survey of recent literature addressing CSR impacts on SHD, we highlight CSR potentials to improve average well-being in multiple dimensions of SHD. Moreover, we critically assess challenges and limitations of CSR as a strategy to preserve and foster SHD. For instance, studies have shown that, despite CSR-driven well-being increases, social capital, relational capabilities and collective agency may become challenged by corporate strategies. Moreover, corporate environmental impacts have been found to be less often addressed by both, companies and SHD researchers. Resulting inequality and fairness issues have been identified as causes of violence against corporations even in the presence of total well-being improvements. We conclude that companies should strategically take into account a comprehensive range of factors driving and hampering SHD to account for their whole portfolio of corporate opportunities and risks. This requires evaluating CSR impacts instead of only focusing on CSR inputs and outputs. Thereby, corporations can mitigate their risks, improve their stakeholder trust and strengthen their competitiveness. Keywords: Corporate Social Responsibility (CSR), CSR impact evaluation, Sustainable Human Development, Base of the Pyramid (BoP), Capability Approach